John Gilissen and the Teaching of Legal History in Brussels - Dhondt, Frederik (Acta Universitatis Lodziensis. Folia Iuridica, 2022)
John Gilissen (1912–1988) was a high-profile legal academic at the Université libre de Bruxelles (°1834) and the Vrije Universiteit Brussel (°1969). Personal – albeit fragmentary – archival records deposited with these universities permit to reconstruct his teaching (both ex cathedra-courses for big groups and intensive tutorials), impressive global scientific network and insatiable scientific curiosity. Gilissen is the author of standard works on many aspects of domestic legal history (both public and private), and acquired renown as the secretary-general of the Société Jean Bodin pour l’histoire comparative des institutions. His influential position as a public prosecutor, law professor and legal historian generates a unique insider’s perspective on the confessional, linguistic and constitutional transformation of the country from World War One to the First Reform of the State. The current law curriculum at the Vrije Universiteit Brussel still bears marks of Gilissen’s comparative approach to the history of civil law and his interest in the contemporary relevance of institutional history.